Home-based and digitally delivered exercise interventions for blood pressure management in adults with hypertension: a systematic review (2021–2026) - Jeki Haryanto; Dally Rahman; Naluri Denay (JRTI (Jurnal Riset Tindakan Indonesia), 2026)
High blood pressure is still a major risk factor that can be changed for heart problems and early death. This systematic review of literature combined the latest evidence on home-based exercise interventions for blood pressure management in adults by looking at different modalities, effects on systolic and diastolic blood pressure, features of a programme that make it effective, and the use of digital delivery technologies. The review used the PRISMA 2020 method. A carefully organized search of Scopus came up with 1858 records. After taking out 3 duplicates, 1855 records were first checked by title and abstract. 126 full-text reports were retrieved for eligibility check. 74 studies have met the inclusion criteria after full-text reading and were included in the qualitative synthesis. Eligible studies enrolled adults with hypertension or elevated blood pressure undergoing home-based or tele-delivered exercise and reporting systolic and/or diastolic outcomes. Methodological adequacy was appraised with the FICO framework. Because of marked heterogeneity in dosing and outcome ascertainment, findings were integrated through thematic synthesis rather than meta-analysis. Four set of main results were drawn. Firstly, aerobic and combined aerobic-resistance exercises were the most prescribed ones, while isometric and mind-body methods displayed differential effects but consistent benefits. Secondly, most controlled studies demonstrated that both systolic and diastolic blood pressure levels were clinically significantly lowered when compared to usual care. Thirdly, the changes seen with exercise were dependent on exercise intensity, frequency, and time as well as adherence that stood out from others, with supervision a d digital monitoring as important moderators. Fourthly, digitally and tele-delivered programmed formed a sizeable part of the evidence and were often used in cardiac, renal, oncological, and metabolic populations. Generally, home-based exercise seems to be an effective addition to managing antihypertensive treatment although further work is required to standardise the prescription of exercise, to find objective ways to measure adherence, and to do long-term studies involving populations from diverse backgrounds.